Nonlinear guided wave optics : a testbed for extreme waves - Wabnitz, S. (IOP (Series). Release 4., 2017)
Experiments and theory have rapidly progressed on nonlinear optical extreme waves, showing that guided wave nonlinear optics and fiber lasers provide a relatively simple, accessible and controllable test bed for the observations and accurate statistical studies of extreme wave phenomena that obey the same universal rules, which apply to a large ensemble of different physical systems. With introductory material to make the subject area accessible to non-specialists such as graduate and PhD students, and researchers working in other areas where extreme waves are relevant, this book features contributions by prominent scientists in this emerging field and is a comprehensive treatment of optical extreme wave research.